Effects of colchicine on gingival inflammation, apoptosis, and alveolar bone loss in experimental periodontitis. Issue 5 (31st May 2018) - Aral, Cüneyt Asım; Aral, Kübra; Yay, Arzu; Özçoban, Özge; Berdeli, Afig; Saraymen, Recep
Abstract: Background: The aim of the study was to investigate the effects of colchicine on cytokine production, apoptosis, alveolar bone loss, and oxidative stress in an experimental model of periodontitis in rats. Methods: Forty‐eight rats were divided equally into four groups: healthy (H); periodontitis (P); periodontitis+colchicine low dose (CL, 30 μg/kg/day), and periodontitis+colchicine high dose (CH, 100 μg/kg/day). After 11 days, interleukin (IL) ‐1β, IL‐8, and IL‐10 were analyzed in gingival samples using Enzyme‐Linked ImmunoSorbent Assay. Receptor activator of nuclear factor kappa‐B ligand (RANKL), osteoprotegerin (OPG), total oxidative stress (TOS), total antioxidant status (TAS), and oxidative stress index (OSI) were measured in gingiva and serum. Alveolar bone volume was evaluated via micro‐CT. Apoptotic cells were detected by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay in histological sections. Results: Colchicine treatment significantly reduced IL‐1β, IL‐8, RANKL, RANKL/OPG, TOS, OSI, and bone volume ratio levels, and increased TAS levels compared to group P (p < 0.05). High dose colchicine treatment (CH) significantly decreased TUNEL+ cell counts compared to group P (p < 0.05). Conclusions: These finding suggest that colchicine has a prophylactic potential for the prevention of periodontal tissue destruction through anti‐inflammatory, anti‐oxidative, anti‐apoptotic, and bone‐protective effects.